The Analisis of Word Choice in Denny Sumargo Podcast Youtube Channe: Analisis of Word Choice in Denny Sumargo Podcast Youtube Channe - Wulandari; Ahada Wahyusari; Fabio Testy Ariance Loren (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
This research aims to describe the accuracy of word choice or diction in Denny Sumargo's podcast. The method in this research is a qualitative descriptive method. The data source in this research is Denny Sumargo's podcast in December 2022-January 2023. The data collection technique for this research is using document techniques. The instrument used in this research is a human instrument, namely the researcher himself, with his knowledge, collects data based on understood criteria regarding word choice or diction contained in Denny Sumargo's podcast. The results of this research prove that there is the use of words with denotative and connotative meaning, the use of words with synonymous meaning, the use of euphemisms, the use of words with generic and specific meaning, and the use of words with concrete and abstract meaning.